Nano-enhanced biocarriers: Ferric oxide-modified chitosan and calcium alginate beads for improved fermentation efficiency and reusability in a bubble column bioreactor - Abutu, David; Aderemi, B. O.; Ameh, A.O; Wan Mohd Hafizuddin, Wan Yussof; Agi, Augustine Aja (Springer, 2025)
Chitosan beads (CB) and calcium alginate beads (CAB) are widely used for immobilizing Saccharomyces cerevisiae in fermentation, but their low mechanical strength and limited surface area reduce ethanol yield. To overcome these limitations, ferric oxide (Fe₂O₃) nanoparticles were incorporated into CB and CAB to enhance both mechanical strength and surface area. The modified carriers were employed for Saccharomyces cerevisiae immobilization in a bubble column bioreactor under semi-batch fermentation conditions at 35 °C, an air flow rate of 0.01 L/min, and pH 4.0 for 15 h. The Fe₂O₃ nanoparticles incorporation significantly improved the rupture forces of CB and CAB, increasing from 2 ± 0.05 N to 8 ± 0.5 N and 2 ± 0.05 N to 9 ± 0.07 N, respectively. The surface area of CB increased from 18 ± 0.3 m2/g to 48 ± 0.2 m2/g, while CAB increased from 2 ± 0.2 m2/g to 50 ± 0.1 m2/g, leading to enhanced cell adsorption from 1.13 × 10⁸ to 1.10 × 10⁹ cells/mL Consequently, ethanol yield improved from 37 ± 0.28% to 45 ± 1.23%. Unlike unmodified CB and CAB, which exhibited significant rupture after five reuse cycles, the modified beads retained their structural integrity and activity, demonstrating their durability for yeast immobilization and reuse. This approach offers a promising strategy for enhancing fermentation efficiency and carrier stability in ethanol production.